Type II Cepheids: period-luminosity-metallicity relations for the Population II distance scale - Das, Susmita; Bhardwaj, Anupam; Marconi, Marcella (Frontiers in Astronomy and Space Sciences, 2026)
Type II Cepheids are a class of pulsating variable stars that play a critical role in our understanding of stellar evolution, distance measurement and tracing the structure and kinematics of old stars in nearby galaxies. This review provides a comprehensive summary of the current state of research on Type II Cepheids, including their observed properties, pulsation mechanisms and their distinction from other variable stars. These pulsating variable stars, found primarily in older stellar populations, exhibit well-defined period-luminosity relations but with an added advantage that they exhibit weak or negligible dependence on metallicity in most passbands. We explore their relevance in the context of their role as distance indicators and potential calibrators of the first rung of the extragalactic distance ladder. Finally, the review highlights recent advancements in theoretical models, observations across different wavelengths and ongoing debates concerning their classification.